Igf2 ligand dependency of Pten(+/-) developmental and tumour phenotypes in the mouse. - Church, D; Phillips, B; Stuckey, D; Barnes, D; Buffa, F; Manek, S; Clarke, K; Harris, A; Carter, E; Hassan, A (2012)
The tumour suppressor PTEN is a key negative regulator of the PI3K-Akt pathway, and is frequently either reduced or lost in human tumours. Murine genetic studies have confirmed that reduction of Pten promotes tumourigenesis in multiple organs, and demonstrated dependency of tumour development on the activation of downstream components such as Akt. Insulin-like growth factors (IGFs) act via IGF1R to activate the PI3K-Akt pathway, and are commonly upregulated in cancer. A context-dependent interplay between IGFs and PTEN exists in normal tissue and tumours; increased IGF2 ligand supply induces Pten expression creating an autoregulatory negative feedback loop, whereas complete loss of PTEN may either cooperate with IGF overexpression in tumour promotion, or result in desensitisation to IGF ligand. However, it remains unknown whether neoplasia associated with Pten loss is dependent on upstream IGF ligand supply in vivo. We evaluated this by generation of Pten(+/-) mice with differing allelic dosage of Igf2, an imprinted gene encoding the potent embryonic and tumour growth factor Igf2. We show that biallelic Igf2 supply potentiates a previously unreported Pten(+/-) placental phenotype and results in strain-dependent cardiac hyperplasia and neonatal lethality. Importantly, we also show that the effects of Pten loss in vivo are modified by Igf2 supply, as lack of Igf2 results in extended survival and delayed tumour development while biallelic supply is associated with reduced lifespan and accelerated neoplasia in females. Furthermore, we demonstrate that reduction of PTEN protein to heterozygote levels in human MCF7 cells is associated with increased proliferation in response to IGF2, and does not result in desensitisation to IGF2 signalling. These data indicate that the effects of Pten loss at heterozygote levels commonly observed in human tumours are modified by Igf2 ligand, and emphasise the importance of the evaluation of upstream pathways in tumours with Pten loss.